Kellers Erzählen Strukturen - Funktionen - Reflexionen - Theisohn, Philipp (Gottfried Kellers Moderne, 2022)
Keller not only reinterpreted literary genres like the legend but, with the bildungsroman and the novella, also shaped the forms that psychologically gauge the modern subject. These contributions explore Keller's texts as evidence of a "threshold narratology," which eludes epochal attributions. Keller's narrative works are thus revealed as a laboratory of transitory poetics.